THE INFLUENCE OF BILINGUALISM ON COGNITIVE PROCESSING: A PSYCHOLINGUISTIC APPROACH - Sianturi, Bella Sonia; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
This research examines the influence of bilingualism on cognitive processing through a psycholinguistic approach, focusing on how managing two or more languages impacts cognitive functions such as attention, memory, problem-solving, and decision-making. Bilingualism requires constant monitoring and control of multiple linguistic systems, which enhances executive functions, including cognitive flexibility, inhibition, and task-switching abilities. This study explores the mechanisms behind language switching, cross-linguistic interference, and metalinguistic awareness, highlighting how these processes shape both linguistic and non-linguistic cognitive skills. By analyzing empirical data from behavioral experiments and neuroimaging studies, the research investigates how bilingualism contributes to neural plasticity, delays age-related cognitive decline, and fosters adaptability in complex environments. The findings aim to provide insights into the cognitive advantages of bilingual individuals and their implications for education, cognitive training, and neuropsychological practices. This study contributes to the understanding of the intricate relationship between bilingual language use and cognitive development, emphasizing its significance for interdisciplinary fields such as linguistics, psychology, and neuroscience.